Josephinische Mandarine Bürokratie und Beamte in Österreich 1848 -1914 - Heindl, Waltraud (2013)
Content of the book are the bureaucracy and its officials in Austria between 1848 - 1914, their mutuel influences in office and private life, cultur, identities and loyalities, as well as questions of images.